2018
DOI: 10.5194/acp-18-17769-2018
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol production from local emissions dominates the organic aerosol budget over Seoul, South Korea, during KORUS-AQ

Abstract: Abstract. Organic aerosol (OA) is an important fraction of submicron aerosols. However, it is challenging to predict and attribute the specific organic compounds and sources that lead to observed OA loadings, largely due to contributions from secondary production. This is especially true for megacities surrounded by numerous regional sources that create an OA background. Here, we utilize in situ gas and aerosol observations collected on board the NASA DC-8 during the NASA–NIER KORUS-AQ (Korea–United States Air… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
155
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(174 citation statements)
references
References 189 publications
(358 reference statements)
15
155
4
Order By: Relevance
“…6.3) were not located outside of the SE US. Similar vertical profile shapes of OA and submicron particles were also observed in a campaign outside the US over South Korea (Nault et al, 2018). Although OA accounted for ∼ 40 % of the total submicron particles, the shape of OA and total submicron particles' vertical profiles were nearly identical.…”
Section: Aerosol Extinction From Satellite Measurementssupporting
confidence: 71%
See 3 more Smart Citations
“…6.3) were not located outside of the SE US. Similar vertical profile shapes of OA and submicron particles were also observed in a campaign outside the US over South Korea (Nault et al, 2018). Although OA accounted for ∼ 40 % of the total submicron particles, the shape of OA and total submicron particles' vertical profiles were nearly identical.…”
Section: Aerosol Extinction From Satellite Measurementssupporting
confidence: 71%
“…This also indicates that SOAs are enhanced near the source regions statistically. Nault et al (2018) also showed the production of HCHO and SOA are similar and plateau around 0.5-1 photochemical days. So, in the near field of emissions and chemistry, the production of these two species is similar; however, outside the near field of emissions and rapid chemistry, the long lifetime of OA vs. the steady state of HCHO would start controlling the slopes and correlations.…”
Section: Temporal Variation Of the Agreement Between Oa Estimate And mentioning
confidence: 73%
See 2 more Smart Citations
“…Equations and are both purely observationally constrained and therefore are not affected by model uncertainties. HR‐AMS‐measured PM 1 OA mass concentration (DeCarlo et al, ; Nault et al, ; Schroder et al, ) is used in equation , and total aerosol surface area (nucleation, Aitken, accumulation modes) calculated from AMP measurements (Brock et al, ; Kupc et al, ; Williamson et al, ) is used in equation . Figure shows the combined results from both ATom‐1 and ATom‐2, excluding measurements below 3 km (where oceanic emissions play an important role).…”
Section: On the Currently Missing Ch3cho Production Mechanismsmentioning
confidence: 99%